For this equation I would assume you use substitution, you plug in what y equals (3x -2), for the y in the second equation (4x - 4y = 8), you now have 4x - 4(3x-2) = -8 you then proceed to factor out this equation, you distribute the -4 and now you have 4x -12x + 8 = -8 you then subtract the -12x from the 4x and the result is -8x + 8 = -8, you then proceed to isolate the x subtracting the 8 from both sides and you now have -8x =-16 you then isolate the x by dividing -8 from both sides, your results are x = 2, you answer isn’t negative 2 because when you divide two negatives they cancel out creating a positive number.